Search for the in-situ production of $$^{77}$$ 77 Ge in the GERDA neutrinoless double-beta decay experiment - M. Agostini; A. Alexander; G. Araujo; A. M. Bakalyarov; M. Balata; I. Barabanov; L. Baudis; C. Bauer; S. Belogurov; A. Bettini; L. Bezrukov; V. Biancacci; et al. (European Physical Journal C: Particles and Fields)
Abstract The beta decay of $$^{77}$$ 77 Ge and $$^{77m}$$ 77 m Ge, both produced by neutron capture on $$^{76}$$ 76 Ge, is a potential background for Germanium based neutrinoless double-beta decay search experiments such as GERDA or the LEGEND experiment. In this work we present a search for $$^{77}$$ 77 Ge decays in the full GERDA Phase II data set. A delayed coincidence method was employed to identify the decay of $$^{77}$$ 77 Ge via the isomeric state of $$^{77}$$ 77 As ( $$9/2^+$$ 9 / 2 + , $${475}\,\hbox {keV}$$ 475 keV , $${T_{1/2} = {114}\,{\upmu }\hbox {s}}$$ T 1 / 2 = 114 μ s , $$^{77m}$$ 77 m As). New digital signal processing methods were employed to select and analyze pile-up signals. No signal was observed, and an upper limit on the production rate of $$^{77}$$ 77 Ge was set at $$<0.216$$ < 0.216 nuc/(kg $$· $$ · yr) (90% CL). This corresponds to a total production rate of $$^{77}$$ 77 Ge and $$^{77m}$$ 77 m Ge of $$<{0.38}$$ < 0.38 nuc/(kg $$· $$ · yr) (90% CL), assuming equal production rates. A previous Monte Carlo study predicted a value for in-situ $$^{77}$$ 77 Ge and $$^{77m}$$ 77 m Ge production of (0.21 ± 0.07) nuc/(kg.yr), a prediction that is now further corroborated by our experimental limit. Moreover, tagging the isomeric state of $$^{77m}$$ 77 m As can be utilised to further suppress the $$^{77}$$ 77 Ge background. Considering the similar experimental configurations of LEGEND-1000 and GERDA, the cosmogenic background in LEGEND-1000 at LNGS is estimated to remain at a sub-dominant level.